2021
DOI: 10.3389/fmed.2021.731412
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcomes After Planned or Emergency Delivery for Placenta Accreta Spectrum: A Systematic Review and Meta-Analysis

Abstract: Objective: To compare maternal and neonatal outcomes for women with placenta accreta syndrome (PAS) delivering via a planned or emergent approach.Methods: A systematic search for relevant studies was conducted by screening the PubMed, Scopus, Web of Science, and Google Scholar electronic databases. Included studies should have been retrospective record-based or prospective in design. They must have compared maternal and/or neonatal outcomes for PAS patients delivering via planned and emergency procedures. Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Infants born to women with an urgent delivery for PAS had worse clinical outcomes including lower gestational age, higher NICU admission, and perinatal mortality. This is consistent with the findings of previous research where a planned delivery for PAS with a multidisciplinary team showed favourable neonatal outcomes when compared with an urgent delivery [ 18 , 20 , 23 , 35 ]. However, it is worth noting that several studies did not find significant differences in neonatal outcomes between the two delivery groups [ 25 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Infants born to women with an urgent delivery for PAS had worse clinical outcomes including lower gestational age, higher NICU admission, and perinatal mortality. This is consistent with the findings of previous research where a planned delivery for PAS with a multidisciplinary team showed favourable neonatal outcomes when compared with an urgent delivery [ 18 , 20 , 23 , 35 ]. However, it is worth noting that several studies did not find significant differences in neonatal outcomes between the two delivery groups [ 25 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with Morlando et al [ 18 ], which found no significant differences in transfusion rates or major morbidity between planned and emergency deliveries among women with PAS. On the contrary, a systematic review and meta-analysis of nine related studies comparing maternal outcomes for PAS patients delivering via planned and emergency procedures showed that women undergoing planned delivery required fewer units of transfused blood, experienced shorter hospital stay durations, and presented reduced risks for maternal ICU admission and severe maternal morbidity [ 20 ]. The review results may be explained by differences in levels of experience of clinicians in PAS management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It mainly explains why the ECD group has lower birth weights and worse perinatal outcomes, because gestational age at delivery is a major determinant of neonatal survival and morbidity. [36,38] In general, our findings are in line with a previous similar meta-analysis by Zhong et al, [39] which focused on the obstetrical outcomes of women with PAS, and the neonatal outcomes were limited by a small sample size of infants. The strength of the current study, on the other hand, is the larger population involved, with an emphasis on all relevant parameters that reflect perinatal condition.…”
Section: Discussionsupporting
confidence: 91%